1990
DOI: 10.1002/em.2850160302
|View full text |Cite
|
Sign up to set email alerts
|

Acrylamide exposure induces a delayed unscheduled dna synthesis in germ cells of male mice that is correlated with the temporal pattern of adduct formation in testis DNA

Abstract: A study of meiotic and postmeiotic germ-cell-stage sensitivity of male mice to induction of unscheduled DNA synthesis (UDS) by acrylamide showed that DNA repair could be detected in early spermatocytes (after the last scheduled DNA synthesis) through about mid-spermatid stages. No DNA repair could be detected in later stages. The maximum UDS response was observed 6 hr after i.p. exposure and was about 5 times greater than the response measured immediately after treatment. This is the longest delay between chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 10 publications
(4 reference statements)
2
33
1
Order By: Relevance
“…A lower frequency of pregnant females obtained after exposure of spermatozoa to AA and X-rays + AA [14] can be compared to a higher frequency of sperm head abnormalities, because malformed spermatozoa are not able to fertilize. Also, the results of other AA studies suggest that the late spermatids and spermatozoa are the most susceptible to damage [13,15,17,[44][45][46] . In previous studies, a significant increase in micronucleus frequency in bone marrow was observed 24 h after treatment with 50-100 mg/kg bw of AA [4,6,7].…”
Section: Discussionmentioning
confidence: 99%
“…A lower frequency of pregnant females obtained after exposure of spermatozoa to AA and X-rays + AA [14] can be compared to a higher frequency of sperm head abnormalities, because malformed spermatozoa are not able to fertilize. Also, the results of other AA studies suggest that the late spermatids and spermatozoa are the most susceptible to damage [13,15,17,[44][45][46] . In previous studies, a significant increase in micronucleus frequency in bone marrow was observed 24 h after treatment with 50-100 mg/kg bw of AA [4,6,7].…”
Section: Discussionmentioning
confidence: 99%
“…injections of 0-125 mg AA/kg b.w. (Sega et al, 1990). The testes were injected with tritiated thymidine either at the time of AA treatment or at later times, up to 48 hours following AA exposure.…”
Section: Genotoxicitymentioning
confidence: 99%
“…The DNA alkylation levels in the testes were about 10-fold lower than in the liver. Based on these results, the authors concluded that AA or, more likely a metabolite, is able to interact with DNA and elicit a UDS response in early spermatocytes through mid-spermatid stages (Sega et al, 1990).…”
Section: Genotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies of genetic effects, DNA adduct formation, and unscheduled DNA synthesis in spermiogenic cells after acrylamide exposure led to the proposal of a glycidamidemediated mutagenic pathway via DNA or protamine alkylation [24][25][26]. Consistent with this hypothesis, glycidamide has been shown to induce dominant lethal mutations in male mice, with the most sensitive stages being spermatozoa of the testis and epididymis [27]; these are the same stages that show the highest sensitivity to dominant lethal induction by acrylamide.…”
Section: Introductionmentioning
confidence: 99%